Establishment and growth of Aonla (Emblica officinalis) as affected by irrigation and mulching in the Shivaliks of Punjab - VASHISHT, B. B.; SINGH, C. B.; BIWALKAR, NILESH (Journal of Soil and Water Conservation, 2018)
The Aonla (Emblica officinalis Gaertn.) is being cultivated as a rain-fed tree crop in the Shivaliks of Punjab. Soil moisture stress is one of the major constraints for early orchard establishment in the region. The present study concerns the identification of optimum level of irrigation with and without polythene mulching for the establishment of aonla in the water scarcity situations. During a typical drying period, a total number of 13, 9 and 5 irrigations based on IW/Pan-E ratio of 0.7 (I0.7), 0.5 (I0.5) and 0.3 (I0.3) were applied to aonla plants. The respective improvement in stock girth and plant height was 67.5 and 82.4% higher by irrigating the plants more frequently at I0.7 than at least frequent regime of I0.3. Respective increase of 43.5 and 58.1% in stock girth and plant height was observed with polythene mulch over no mulch after two years of plantation. The stock girth and plant height was significantly higher by 32.0 and 48.27% by irrigating the aonla plants at I0.5 with mulching than irrigating at I0.7 without mulching. This resulted in saving of 20 cm of irrigation water (four irrigations) on net area basis during a typical drying period. With this saving of water, additional area of the orchard may be established.